Assessment of the main reasons for the stagnation of territorial development in Russia - Misakov, Anzor V,; Sabanchiev, Anzor Kh; Sanginova, Lola D.; Danilevskaya, Elena N.; Eskiev, Musa A. (Revista de la Universidad del Zulia, 2020)
Globalization, accompanied by a continuous increase in competition, complicates the conditions for the development of market relations in the Russian Federation. The priority development territories should have functioned as a tool for industrial and productive reform. These territories and their special economic zones should have become territorial centers of innovative and industrial development. However, it does not happened. The article analyzes some of the main reasons for this situation in Russia.